Prediction of changes in central hemodynamics in overweight men with further development of obesity - Nemesh, Marianna; Palamarchuk, Olga; Kentesh , Oksana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. There is a wide range of anthropometric methods for determination overweight and obesity. The most popular are body mass index, waist and hip circumference or waist-hip ratio and the measurement of body composition using bioimpendance method. Each of these methods has a lot of pros and cons, but none of them is the «gold standard». Therefore, it is not enough to rely only on the results of indirect methods to assess the state of the human body. They should be taken into account with laboratory or diagnostic methods, to better assess the morpho-functional features of the human body. The aim. To determine the relationship between central hemodynamic parameters and indices obtained by bioimpedance and anthropometric methods in order to predict changes in central hemodynamics in overweight men with the further development of obesity. Materials and methods of the research. 49 men aged 18–25 were examined. Body component composition was measured using Tanita BC-601 analyzer scales. Also body mass index and waist, hip circumference were measured. The indices of the cardiovascular system were determined using the rheographic complex «REOKOM», the method of tetrapolar rheography according to Kubicek. The results of the study were statistically processed using correlation and multifactor regression analysis. Results. According to the results of multifactor regression analysis, it was found that waist circumference and the index of visceral fat were associated with indices of cardiac index and the index of workload of left ventricular and the index of the peripheral vascular resistance (p < 0.05). Waist circumference and index of visceral fat had negative correlations with total peripheral resistance (r = -0,351 and r = -0,34, p < 0,01). Moreover, waist circumference and the index of visceral fat have positive correlation with cardiac output and the workload of left ventricle (r = 0,543, p < 0,001; r = 0,378, p < 0,001). Conclusions. Waist circumference and indices of visceral fat and subcutaneous fat in the trunk are the most accurate methods for predicting in future not only abdominal obesity but also an increase in workload of the left ventricle, cardiac output, and decreased vascular resistance.